A rare bacteremia caused by Fannyhessea vaginae in a pregnant woman: case report and literature review - Liu, Peng; Wang, Lina; Li, Rongguo; Chen, Xiaodi (Frontiers in Cellular and Infection Microbiology, 2023)
Bloodstream infection caused by anaerobic microorganisms continues to be associated with a high mortality risk, necessitating a rapid diagnosis and an appropriate treatment. As an anaerobic grampositive organism associated with vaginal infections, Fannyhessea vaginae is a rare cause of invasive infections. In this case, a 32-year-old pregnant woman with bacterial vaginosis presented with bacteremia. The microbiological analysis of the blood cultures identified F. vaginae. The patient was treated empirically with 5 days of cefoperazone/sulbactam and recovered well. Here, we provide a review of the literature on F. vaginae infections, and the reported cases demonstrate the need for awareness of the different anaerobic species found in the vaginal tract and adaptation of empirical therapies, especially in pregnant women.